2020
DOI: 10.1155/2020/8877862
|View full text |Cite
|
Sign up to set email alerts
|

Iron (III)-Quercetin Complex: Synthesis, Physicochemical Characterization, and MRI Cell Tracking toward Potential Applications in Regenerative Medicine

Abstract: In cell therapy, contrast agents T1 and T2 are both needed for the labeling and tracking of transplanted stem cells over extended periods of time through magnetic resonance imaging (MRI). Importantly, the metal-quercetin complex via coordination chemistry has been studied extensively for biomedical applications, such as anticancer therapies and imaging probes. Herein, we report on the synthesis, characterization, and labeling of the iron (III)-quercetin complex, “IronQ,” in circulating proangiogenic cells (CAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 108 publications
2
34
1
Order By: Relevance
“…It has been shown that IronQ can act as a stimulating agent by favoring the proangiogenic cell differentiation of PBMCs. Moreover, IronQ is highly sensitive and has no toxicity but enhanced the therapeutic e ciency of labeled cells [29]. These results are suggesting that IronQ exerts the most outstanding excellent dual functions in applications of cell-based therapy.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been shown that IronQ can act as a stimulating agent by favoring the proangiogenic cell differentiation of PBMCs. Moreover, IronQ is highly sensitive and has no toxicity but enhanced the therapeutic e ciency of labeled cells [29]. These results are suggesting that IronQ exerts the most outstanding excellent dual functions in applications of cell-based therapy.…”
Section: Discussionmentioning
confidence: 89%
“…PBMCs cultured under IronQ complex results in accelerating proliferative of adherent spindle-shaped cells and number of early outgrowth colonies (CFU-Hill) Firstly, the appropriate concentration of the Iron-Quercetin complex (IronQ) was determined by cytotoxicity assay in a previous study [29]. We found that 125 µg/mL of IronQ complex is not toxic to peripheral blood mononuclear cells (PBMCs) when cultured for a long time (i.e., for one month).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the appropriate concentration of the iron-quercetin complex (IronQ) was determined by cytotoxicity assay in a previous study [33]. We found that 125 µg/mL of IronQ complex was not toxic to peripheral blood mononuclear cells (PBMCs) when cultured for a long time (i.e., for one month).…”
Section: Pbmcs Cultured With the Ironq Complex Show The Accelerating Proliferation Of Adherent Spindle-shaped Cells And The Number Of Earmentioning
confidence: 99%
“…IronQ modulates the cellular characteristics of PBMCs to enrich the blood-derived spindle-shape-like cells (EPCs) during in vitro expansion. Simultaneously, there is the potential to visualize IronQ-labeled cells that have been transplanted with MR imaging via the paramagnetic properties of IronQ [33]. The iron-quercetin complex has some practical advantages over other types of MRI contrast agents when used for clinical purposes.…”
Section: Introductionmentioning
confidence: 99%